Watercolor techniques : painting light and color in landscapes and cityscapes - Reardon, Michael, 1955- (Cincinnati, Ohio : North Light Books, 2016)
Provides basics of tools, color chemistry, and techniques, advances into perspective, color values, and architectural details, and includes eight start-to-finish demonstrations to practice those skills--
-- Setting up: getting to know your materials -- The secret world of paints: unlocking their mysteries -- Laying it down: exploring basic techniques -- The architecture of watercolor -- The value of light -- Values at work -- Color in the architectural landscape -- The alllure of color -- Building light.
Includes index.
Keywords: Watercolor painting -- Technique; Landscape painting -- Technique